2022
DOI: 10.1002/anie.202114538
|View full text |Cite
|
Sign up to set email alerts
|

Electropolymerization of Metal Clusters Establishing a Versatile Platform for Enhanced Catalysis Performance

Abstract: Atomically precise metal clusters are attractive as highly efficient catalysts, but suffer from continuous efficiency deactivation in the catalytic process. Here, we report the development of an efficient strategy that enhances catalytic performance by electropolymerization (EP) of metal clusters into hybrid materials. Based on carbazole ligand protection, three polymerized metal-cluster hybrid materials, namely Poly-Cu 14 cba, Poly-Cu 6 Au 6 cbz and Poly-Cu 6 Ag 4 cbz, were prepared. Compared with isolated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 66 publications
0
34
0
Order By: Relevance
“…This packing allowed both the Au 1 S 2 motifs and the S 1 –Au 1 –S 1 unit in the kernels to spiral along the a -axis to form the triple-helical linear structure. Of note, it was observed that other alkynyl-protected Au 6 Cu 6 nanoclusters that lacked intercluster interactions (with only some C–H···π interactions) did not assemble into polymer chains in the crystal lattice (Figure S12), , confirming that the abundant intermolecular interactions between Au 6 Cu 6 (4-MeOBT) 12 nanoclusters played a significant role in its assembly into a triple-helical structure.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…This packing allowed both the Au 1 S 2 motifs and the S 1 –Au 1 –S 1 unit in the kernels to spiral along the a -axis to form the triple-helical linear structure. Of note, it was observed that other alkynyl-protected Au 6 Cu 6 nanoclusters that lacked intercluster interactions (with only some C–H···π interactions) did not assemble into polymer chains in the crystal lattice (Figure S12), , confirming that the abundant intermolecular interactions between Au 6 Cu 6 (4-MeOBT) 12 nanoclusters played a significant role in its assembly into a triple-helical structure.…”
Section: Resultsmentioning
confidence: 90%
“…Specifically, as shown in Figure 3A,B, the presence of π−π unit in the kernels to spiral along the a-axis to form the triplehelical linear structure. Of note, it was observed that other alkynyl-protected Au 6 Cu 6 nanoclusters that lacked intercluster interactions (with only some C−H•••π interactions) did not assemble into polymer chains in the crystal lattice (Figure S12), 44,45 S2), indicating that the self-assembly of Au 6 Cu 6 (4-MeOBT) 12 nanoclusters was most thermodynamically favorable. Moreover, Figure 3D shows that the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energy levels and the HOMO−LUMO energy gap of the [Au 6 Cu 6 (4-MeOBT) 12 ] 2 dimer were similar to those of the Au 6 Cu 6 (4-MeOBT) 12 monomer, but the distributions of these frontier molecular orbitals (MOs) were different.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Both geometric and electronic structures play crucial roles in determining the catalytic properties of nanoparticles [1–14] . However, the two factors are often convoluted, and it is thereby difficult to precisely study the contribution of one factor to the overall catalytic performance at a time.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the presence of the nitrate reduction reaction and is consistent with previous findings regarding the NO 3 RR of metal-based cathodes. [20] What's more, electrochemical impedance spectroscopy (EIS) shows that Fe@Gnc has a lower resistance than pure graphene, Fe and Fe/G electrocatalytic materials, implying that Fe@Gnc has a higher charge transfer capability (Figure S20b). The growth in the size of Fe nanoparticles in Fe/G leads to a significant increase in the resistance of charge diffusion to reach the active site.…”
Section: Resultsmentioning
confidence: 99%